The Oxford handbook of the history of nationalism - Breuilly, John 1946- Hrsg (Oxford Univ. Press, 2013)
This title comprises thirty six essays by an international team of leading scholars, providing a global coverage of the history of nationalism in its different aspects - ideas, sentiments, politics. Every chapter takes the form of an interpretative essay which, by a combination of thematic focus, comparison, and regional perspective enables the reader to understand nationalism as a distinct and global historical subject. The book covers the emergence of nationalist ideas, sentiments, and cultural movements before the formation of a world of nation-states as well as nationalist politics before and after the era of the nation-state, with chapters covering Europe, the Middle East, North-East Asia, South Asia, South-East Asia, and the Americas. Essays on everyday national sentiment and race ideas in fascism are accompanied by chapters on nationalist movements opposed to existing nation-states, nationalism and international relations, and the role of external intervention into nationalist disputes within states